Manual Sobre A Técnica De Aplicação Da Bota De Unna Em Pacientes Com Úlceras Venosas - Martins Junior, Edmundo [UNIFESP] (2018)
Introduction: Caring for people with skin lesions caused by diseases of the lymphatic and venous systems is a challenge. Several studies deal with the importance of compression therapies, but few of them describe Unna’s Boot application technique and the importance of the different materials used in this therapy, thus contributing to the underutilization of the technique. The use of manuals is one of the strategies that provide guidance for professionals. Objective: To develop a manual for Unna’s Boot application technique in patients with venous ulcers for health professionals. Methods: This descriptive study on the development of a manual was approved by the Research Ethics Committee of UNIFESP (CAAE: 92331318.5.0000.5505). Relevant content was obtained by searching the Cochrane Library Database, Scielo, LILACS, PubMed, and Google Scholar. Articles in Portuguese, Spanish and English from 2000 to 2018 were selected for the study. The text, illustrations and photographs, layout, and the recording and editing of a video were then prepared. The developed manual was validated by experts using the Delphi technique and the Content Validity Index (CVI). Results: The manual was validated by the experts in two rounds of the Delphi technique with an overall CVI of 0.98 and was considered adequate regarding content, appearance, and relevance, providing information for health professionals on Unna’ Boot application technique in patients with venous ulcers. The manual has 29 pages including text and illustrations. In addition, a video demonstrating the technique was created. Conclusion: A manual for Unna’ Boot application technique in patients with venous ulcers for health professionals was developed.